Seasonal influence on chemical composition and sanitary quality of bovine milk of the Lerma´s Valley, Argentina (FAVE Sección Ciencias Veterinarias, 2020)
The aim of this study was to determine the seasonal influence in bovine milk composition and sanitary quality for Lerma Valley basin. Samples sent by dairy industries to National University of Salta Milk Laboratory during spring (Pr, n: 104), summer (Ve, n: 131) and winter (In, n: 118) of the years 2017 and 2019 were analyzed. Fat (% F) and protein (% P) percentages, freezing point (FP) and somatic cell count / ml (RCS / ml) were determined. Statistical analysis was performed using the InfoStat 2019p program. The model responded to a CRD. % F and % P were analyzed by ANOVA, while for FP and SCC  non-parametric ANOVA from Kruskal Wallis was used. Tukey Test (p